Psychological symptoms in perimenarcheal adolescents: association with PCOS risk factors - Vanden Brink, Heidi; McCormick, Kathleen C.; Lujan, Marla E.; Chang, Jane; Ipp, Lisa; Mudrak, Erika L.; Alladeen, Anisah; Lamar, Hannah; Kim, Joy Y.; Mendle, Jane (Frontiers in Endocrinology, 2025)
IntroductionPCOS is linked with disproportionately high rates of depression and anxiety that significantly compromise quality of life and pose problems for treatment eligibility and adherence. The overarching objective of the proposed manuscript is to define the presence and severity of psychological symptoms in peri-menarcheal adolescents, and their association with well-described risk-factors for future PCOS.MethodsFifty-two pre- and early post-menarcheal participants underwent a non-fasting blood draw to measure reproductive hormones (Anti-Mullerian Hormone (AMH), Luteinizing Hormone (LH), Follicle Stimulating Hormone (FSH), Total Testosterone, Sex Hormone Binding Globulin (SHBG) and HbA1c, anthropometry, menstrual history (if post-menarcheal), and a series of surveys to evaluate depression (CES-DC), anxiety (MASC) and, as a novel approach, rumination, which is a transdiagnostic psychological process and early prodromal risk for psychological disorders. Parents/legal guardians completed a demographics survey. Random Forest analysis was used to predict depression, anxiety, and rumination from a predetermined set of variables in this participant sample.ResultsThe overall R2 for depression, anxiety, and rumination from the random forest model were 0.557, 0.555, and 0.597, respectively, suggesting overall good explanatory power for psychological outcomes. Parent education (Portion Sum of Squares (SS) = 11.4%) followed by AMH (Portion SS = 10.9%) and waist-hip-ratio (WHR) (Portion SS = 9.2%) were the most important variables in predicting depression. LH: FSH ratio was the most important variable in the dataset used to differentiate participants along the observed anxiety score continuum (Portion SS = 0.112 (11%) followed by HbA1c (Portion SS = 8.1%) and WHR (Portion SS = 7.9%). SHBG was the most frequently identified variable to differentiate participants reporting rumination (Portion SS = 13.3%) followed by Free Androgen Index (Portion SS = 6.9%) and WHR (Portion SS = 6.9%). Adolescents at high risk for progression to PCOS may already experience psychological vulnerabilities prior to a clinical diagnosis or full manifestation of PCOS. Our study findings highlight PCOS as a lifelong, multifaceted health condition with ramifications earlier than commonly documented.